Brain functional changes in patients with Crohn's disease: A resting‐state fMRI study - Lu Li; Jie Ma; Jian‐Guang Xu; Yan‐Ling Zheng; Qian Xie; Lan Rong; Zong‐Hui Liang (Brain and Behavior, 2021)
Abstract Background Crohn's disease (CD) is a chronic recurrent intestinal inflammatory disease, often accompanied by poor adaptation and excessive stress response. However, the potential neurological mechanisms of these symptoms have not yet been studied in‐depth. Objective To investigate alterations in brain activity in patients with Crohn's disease and study the relationship between altered regions and clinical indices. Methods A total of 15 CD patients and 26 matched healthy controls were recruited. All participants underwent fMRI scans. The amplitude of low‐frequency fluctuations (ALFF) and regional homogeneity (ReHo) assessed differences in spontaneous regional brain activity. Differences between the groups were selected as seeds for functional connectivity (FC) analyses. Correlations between disease duration and ALFF/ReHo/FC values in abnormal regions were analyzed. Results Patients with CD had significantly higher ALFF values in the left superior frontal gyrus, anterior cingulate cortex, and supplementary motor area, and lower values in the left hippocampus. They also had higher ReHo values in the left anterior cingulate cortex, supplementary motor area, putamen, and the bilateral superior frontal gyri. FC strength in the left precentral and middle temporal gyri was found to be increased when the left superior frontal gyrus was used as the seed point. FC strength was also observed to be increased in the left postcentral, middle frontal gyri, inferior frontal orbital cortex, and right rolandic operculum when the left anterior cingulate cortex was used as the seed point. Conclusion CD demonstrated abnormal neural activity and FC in various regions primarily associated with emotional, pain and cognitive‐related functions, which provides more information to further understand the neural mechanisms of the disease.